2018
DOI: 10.35680/2372-0247.1290
|View full text |Cite
|
Sign up to set email alerts
|

Can an interactive application be used to collect meaningful feedback from paediatric patients and their parents in a hospital setting?

Abstract: The objective of this study was to determine the acceptability of using an interactive application (Fabio the Frog) to understand the experiences and perspectives of children and parents/carers regarding their health care encounter for the purpose of quality improvement and consumer feedback. Children's perspectives of their healthcare were collected via the interactive application through the use of a validated survey, the Children's Perceptions of Healthcare Survey (CPHS). The acceptability of eliciting view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…However, the emerging literature on interactive learning programs suggests that the questionnaire would be easier for children to answer if the questions and overall structure reflected the child’s stage of development [ 5 , 13 , 16 ]. From these insights, a survey was created to test whether pediatric patients report perceiving the quality of their hospital experiences differently from their parents by capturing both the child patient’s and the parent or guardian’s feedback using an interactive learning game based on the pediatric patient’s proximal zone of development [ 17 , 18 , 19 ]. This paper will report the results of an interactive Qualtrics survey to test the differences in perceived hospital experience between the child patient and their parent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the emerging literature on interactive learning programs suggests that the questionnaire would be easier for children to answer if the questions and overall structure reflected the child’s stage of development [ 5 , 13 , 16 ]. From these insights, a survey was created to test whether pediatric patients report perceiving the quality of their hospital experiences differently from their parents by capturing both the child patient’s and the parent or guardian’s feedback using an interactive learning game based on the pediatric patient’s proximal zone of development [ 17 , 18 , 19 ]. This paper will report the results of an interactive Qualtrics survey to test the differences in perceived hospital experience between the child patient and their parent.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found evidence suggesting that most studies used questionnaires with language too advanced for small children to understand quickly and efficiently [ 16 ]. Emerging studies suggest that interactive learning programs can help engage child patients in health literacy by lowering language barriers and connecting the question domains to the child patients’ proximal zone of development [ 17 , 18 , 19 ]. Using tools that engage pediatric patients at their level of development can enhance the quality of their hospital feedback by reducing barriers to survey engagement related to age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased focus on PREMs is not evenly spread, with some populations or clinical areas not typically included in PREMs collection [ 9 ]. One such area is paediatric care, which, despite internationally agreed statements on the rights of children to be consulted and involved in decision making, and agreement by health services researchers of the need to include children’s views, remain an underrepresented group [ 10 , 11 ]. There are several possible reasons for this: a residual view that children are not sufficiently developed to be able to meaningfully contribute [ 12 ]; comparatively little evidence on the best mechanisms for collecting paediatric experience data [ 10 ]; and, perceived and real challenges in enabling children to adequately describe their experiences to adults collecting such data.…”
Section: Introductionmentioning
confidence: 99%
“…One such area is paediatric care, which, despite internationally agreed statements on the rights of children to be consulted and involved in decision making, and agreement by health services researchers of the need to include children’s views, remain an underrepresented group [ 10 , 11 ]. There are several possible reasons for this: a residual view that children are not sufficiently developed to be able to meaningfully contribute [ 12 ]; comparatively little evidence on the best mechanisms for collecting paediatric experience data [ 10 ]; and, perceived and real challenges in enabling children to adequately describe their experiences to adults collecting such data. However, studies have shown that even young children have the capacity to understand their condition and care [ 13 ], and children’s comments are coherent and pertinent to hospitalization experiences [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%